High stability of Mo-F dual-doped O3-type NaNi1/3Fe1/3Mn1/3O2 cathode material for sodium-ion battery. (August 2022) - Li, Weidong; Chen, Qiuyi; Zhang, Dongyun; Fang, Chen; Nian, Song; Wang, Wenxu; Xu, Cong; Chang, Chengkang
Abstract: Aiming for promoting the capacity and cycling stability of O3-type NaNi1/3 Fe1/3 Mn1/3 O2 (NFM), the cathode material of sodium ion batteries (SIBs) with the most potential for industrialization, Na(Ni1/3 Fe1/3 Mn1/3 )0.99 Mo0.01 O1.99 F0.01 (NFM-MoF), Na(Ni1/3 Fe1/3 Mn1/3 )0.99 Mo0.01 O2 (NFM-Mo) and NaNi1/3 Fe1/3 Mn1/3 O1.99 F0.01 (NFM-F) were successfully synthesized by solid phase method. The electrochemical performance of the doped samples was compared with that of the pristine NFM. The mechanism of the single- or dual-doping was explored by XRD Rietveld refinement and XPS. The NFM-MoF exhibits the highest initial specific discharge capacity of 137mAhg −1 at 1 C with a retention of 91.97% after 100 cycles and the smallest polarization (0.32 V), which could be contributed to the highest Ni 2+ content and highest D Na + (7.335 ×10 −13 cm 2 ·s −1 ) caused by the synergistic effect of Mo and F dual-doping. The highest Fe 3+ content in the NFM-Mo leads to the higher initial discharge capacity of 1 36 mAhg −1 at 1 C with a relative lower retention of 83.38%, which is due to the structure instability resulting from Fe migration and the lowest Mn content, than that of the NFM-F (85.31%). It illustrates that the Mn 4+ plays a crucial role in stabilizing the structure during Na + migrating. The superiority of the discharge capacity of the NFM-Mo become narrow with rates rise, due to its lower D Na + (4.229 ×10 −13 cm 2 ·s −1 ) than that of the NFM-F D Na + (5.681 ×10 −13 cm 2 ·s −1 ). It verifies that it is a diffusion control process at high rates. Mo and F dual-doping in NFM was proved to amplify the benefit of Ni 2+ increasing, meanwhile restrain undesirable Fe increasing due to the synergistic effect. Graphical Abstract: ga1 Highlights: The doped samples show higher capacity and stability than the pristine NFM. The NMF-MoF shows initial 137mAhg −1 at 1 C with 91.97% retention after 100 cycles. The synergistic effect of dual-doping leads to the highest D Na + (7.335 ×10 −13 cm 2 ·s −1 ). The high retention 85.31% of NFM-F is due to the high D Na + caused by cell shrinking. The increasing of Fe 3+ in the NFM-Mo brings high capacity and relative instability.